Non-small Cell Carcinoma of Lung in a 19-year-old Male Presented as Malignant Pleural Effusion - Kabir, Ahmed Imran; Sarkar, Shish Mohammad; Hasan, Md Nazmul; Hossain, AKM Mosharraf (Bangladesh Medical Journal, 2019)
Bronchial carcinoma is rare in younger age group. Smoking, environmental and occupational exposure are the major risk factors. Radiological imaging, bronchoscopy, FNAC and biopsy are the main mode of investigations. Surgery, radiotherapy and chemotherapy are the treatment of choice. Here, we report a case of 19-yearrs-old male and diagnosed as a case of non-small cell carcinoma of lung (NSCC). Cytological examination of pleural fluid showed non-small cell carcinoma. This may be indicating the changing trend of developing NSCC in young adults. Bangladesh Med J. 2018 May; 47 (2): 41-43